PENGARUH PENGGUNAAN INSTAGRAM TERHADAP MINAT AUDISI MOJANG JAJAKA KOTA BOGOR 2019 - Fadrin, Sarah; Lestari, Rochmah Sri; Boer, Rino F. (2021)
Instagram Usage is very influential in the development of digital age as it is today. One of the Tourism Ambassadors of Bogor City, Mojang Jajaka Bogor City also used Instagram to communicate with the public. One of them is Pasanggiri Mojang Jajaka Bogor City information for open audition registration. In this study, the researcher discusses “The Influence of Instagram Usage on Mojang Jajaka Bogor City Audition Interest in 2019” and the research is aimed to find out how much influential is Instagram to attract the interest of Mojang Jajaka Bogor City audition. The theory used in this research is Stimulus-Organism-Response concepts namely media effects, new media, computer mediated communication or CMC and the concept of interest. This research uses quantitative method by distributing questionnaires to 100 respondents. The result of this study indicates that the use of Instagram has a positive effect on interest in audition for Mojang Jajaka Bogor City in 2019 by 28,6%.